2006
DOI: 10.1124/mol.106.030015
|View full text |Cite|
|
Sign up to set email alerts
|

The Tumor Proteasome Is a Primary Target for the Natural Anticancer Compound Withaferin A Isolated from “Indian Winter Cherry”

Abstract: Withaferin A (WA) is a steroidal lactone purified from medicinal plant "Indian Winter Cherry" that is widely researched for its variety of properties, including antitumor effects. However, the primary molecular target of WA is unknown. By chemical structure analysis, we hypothesized that Withaferin A might be a natural proteasome inhibitor. Computational modeling studies consistently predict that C 1 and C 24 of WA are highly susceptible toward a nucleophilic attack by the hydroxyl group of N-terminal threonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
176
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(186 citation statements)
references
References 35 publications
10
176
0
Order By: Relevance
“…Indeed, it has been widely reported that ER stress is implicated in antitumoral effects of proteasome inhibitors. [34][35][36] Consistent with previous research, 21,22 the present study demonstrated that WA inhibited proteasome activity and accumulation of ubiquitinated proteins in PC cells. Subsequent investigations revealed that CHX attenuated WA-induced cell death, indicating that proteotoxicity is important for the effect of WA.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Indeed, it has been widely reported that ER stress is implicated in antitumoral effects of proteasome inhibitors. [34][35][36] Consistent with previous research, 21,22 the present study demonstrated that WA inhibited proteasome activity and accumulation of ubiquitinated proteins in PC cells. Subsequent investigations revealed that CHX attenuated WA-induced cell death, indicating that proteotoxicity is important for the effect of WA.…”
Section: Discussionsupporting
confidence: 81%
“…21 Thus, we sought to determine whether the incomplete autophagy induced by WA was associated with proteasome inhibition. As shown in Fig.…”
Section: Wa Inhibits Proteasome Activity and Induces Er Stress-relatementioning
confidence: 99%
See 1 more Smart Citation
“…Wit A, a steroidal lactone isolated from medicinal plant 'Indian Winter Cherry', has anti-inflammatory and anti-tumor effect (Yang et al, 2007). Several studies have reported that Wit A can induce cancer cell death (Mohan et al, 2004;Sharada et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study conducted in nude mice, intraperitoneal administration of WFA [4-8 mg/kg/day] for 24 days resulted in over 70% inhibition of PC3 subcutaneous tumor growth [57].…”
Section: A B Cmentioning
confidence: 99%